(untitled) (Pedagogical Horizons, 2021)
As a starting point, this article states increasing social divisions as well as increasing mutual networks and dependencies in global spaces: In addition to the controversial debates on climate change that have been taking place around the world for several years, current developments also show both social fractures and interdependencies that the global world society is facing. On the one hand, the principle of controversy proves to be a relevant didactic instrument for Global Citizenship Education. At the same time, however, this article argues that civic education can only take into account the simultaneous coincidence of social divisions on the one hand and mutual social dependencies on the other if the principle of orientation towards political action is also considered. How can teaching and learning procedures be composed that emphasize practical communication and negotiation processes as well as strategies for joint social action? And which bias or dangers must be taken into account when updating the principle of orientation towards political action? Finally, a lesson planning concept provides some food for thought in order to update action-oriented teaching sequences that focus on interdependence in civic education.